Financial Solvency of Russian Regions in 2010-2014: Continued Classification Analysis - I. A. Vinyukov; E. V. Maevsky; P. V. Jagodowsky (Мир новой экономики)
This article is a continuation of the first work done on the State task of the Financial University of 2013 [1-3], in which the classification of the regions of the Russian Federation according to the state statistics for 2005-2011 was proposed. Over the past period, the relevance of the issues has not decreased, and Russia’s gap in the number of subjects of the federation from the nearest “pursuers” (USA, Brazil, Germany, Canada) with the addition of the Crimea has only increased. Classification analysis of Russian regions remains a time-consuming task, as each region is unique in something and it is difficult to find something in common. We continued the analysis of the period data from 2005 to 2011 (before the crisis, the crisis and the initial stage of recovery), and also supplemented it with data from 2012-2014 about a new crisis. We wanted to advance in obtaining a tool for monitoring the financial viability of the regions and to test it in real and changing conditions. Work is continued also to assess the quality of statistical data contained in the Rosstat database, which precedes the classification analysis itself.